Imaging acute complications in cancer patients: what should be evaluated in the emergency setting? - Guimaraes, Marcos D (Cancer Imaging, 2014)
Increased incidence world-wide of cancer and increased survival has also resulted in physicians seeing more complications in patients with cancer. In many cases, complications are the first manifestations of the disease. They may be insidious and develop over a period of months, or acute and manifest within minutes to days. Imaging examinations play an essential role in evaluating cancer and its complications. Plain radiography and ultrasonography (US) are generally performed initially in an urgent situation due to their wide availability, low cost, and minimal or no radiation exposure. However, depending on a patient’s symptoms, evaluation with cross-sectional imaging methods such as computed tomography (CT) and magnetic resonance imaging (MRI) is often necessary. In this review article, we discuss some of the most important acute noninfectious oncological complications for which imaging methods play an essential role in diagnosis.